DAMPAK PERKEMBANGAN E-COMMERCE TERHADAP PERAN AKUNTAN MANAJEMEN - Agung Mersia Mahendradata; Djohan Mashudi; Dwi Suhartini (Universitas Kristen Krida Wacana, 2018)
E-commerce is a “trend” of the market that appeals to the “contemporary” business. E-commerce business increase the transactions through networks result in exploitation in various aspects of control. In this way, e-commerce is vulnerable to issues about the fraudulent practices. This research is expected to contribute to the development of knowledge about the role of management accountants and e-commerce in the future. The role of management accountants faces new challenges facing e-commerce especially in terms of ability to deal with fraud and internal control. This research analyses development of e-commerce and the role of management accountant in Indonesia. The purpose of this study is to find out e-commerce and its impact on the role of management accountants in the e-commerce business in Indonesia. This research uses content analysis approach, because there is multidisciplinary science in researching this research.Keywords : Content Analysis, E-commerce, Internal Control, Management Accountant